RANCANG BANGUN SISTEM INFORMASI MANAJEMEN SURAT BERBASIS WEB PADA KANTOR BPJS KETENAGAKERJAAN CABANG SUKABUMI - Wafa Pamulasari; Nana Suryana (UNIVERSITAS KEBANGSAAN, 2020)
Abstract: Based on the regulation of the State Minister for Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 6 of 2011 concerning General Guidelines for Electronic Service Manuscripts within government agencies, the government requires all government agencies to draw up their respective electronic service manuscripts (correspondence administration information systems) , which refers to the guidelines in the regulation. In the process of official script administration carried out by the BPJS Employment Branch of Sukabumi City is the disposition of correspondence. Disposition is one of the important information notification media for this government agency. The disposition problem that occurs at the BPJS Employment of the Sukabumi City branch is a disposition process that requires a long time. This study aims to make it easier for secretaries, branch heads, department heads, and BPJS Employment staff to see the disposition of letters and manage existing correspondence data. Design and Development of Disposition Information Systems This letter uses the Waterfall system development method with UML (Unified Modeling Language) Tools. From the results of this website-based letter disposition system research can assist in the management, storage and search of letter archives at the BPJS Employment Office of the Sukabumi City branch.Keywords: Information systems, letters, dispositionsAbstrak : Berdasarkan peraturan Menteri Negara Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Republik Indonesia Nomor 6 Tahun 2011 tentang Pedoman Umum Tata Naskah Dinas Elektronik di lingkungan instansi pemerintah, pemerintah mewajibkan semua instansi pemerintahan untuk menyusun tata naskah dinas elektronik (sistem informasi administrasi persuratan) masing-masing, yang mengacu pada panduan dalam peraturan tersebut. Pada proses tata naskah dinas yang dilaksanakan oleh BPJS Ketenagakerjaan Cabang Kota Sukabumi ialah disposisi persuratan. Disposisi merupakan salah satu media pemberitahuan informasi yang penting bagi suatu instansi pemerintahan ini. Permasalahan disposisi yang terjadi pada BPJS Ketenagakerjaan cabang Kota Sukabumi adalah proses disposisi yang membutuhkan waktu yang lama. Penelitian ini bertujuan untuk memudahkan sekretaris, kepala cabang, kepala bidang, dan staf BPJS Ketenagakerjaan untuk melihat disposisi surat dan mengelola data persuratan yang ada. Rancang Bangun Sistem Informasi Disposisi Surat ini menggunakan metode pengembangan sistem Waterfall dengan Tools UML (Unified Modeling Language). Dari hasil penelitian sistem disposisi surat berbasis website ini dapat membantu dalam pengelolaan, penyimpanan serta pencarian arsip surat pada Kantor BPJS Ketenagakerjaan cabang Kota Sukabumi..Kata Kunci : Sistem Informasi, surat, disposisi